Enhancing university teaching : lessons from research into award-winning teachers - Kember, D. David. Kember; McNaught, C. Carmel McNaught (London ; New York : Routledge, 2007)
"In response to demands upon universities to improve the quality of teaching, several governments have attempted to find acceptable measures of what constitutes good university teaching, but have had difficulty doing so. Educational theorists have derived many models of good teaching which diverge widely." "Enhancing University Teaching aims to fill this vacuum by deriving a model of good university teaching from 62 academics, chosen by their universities as their best teachers. These award-winning teachers encompass all major discipline areas and interviews with them have resulted in ten common principles of good university teaching."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: College teaching; Effective teaching